2019
DOI: 10.1111/aos.14271
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography analysis of inner and outer retinal layers in eyes with chiasmal compression caused by suprasellar tumours

Abstract: Purpose: To compare postoperative macular thickness measurements of inner and outer retinal layers in eyes of patients with chiasmal compression with or without visual field (VF) recovery and healthy controls using optical coherence tomography (OCT). Methods: Macular spectral-domain OCT has been used for the auto-segmentation of images obtained from 100 eyes affected with chiasmal compression compared with 100 healthy controls enrolled in this study. We have divided eyes with chiasmal compression into two grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Some reports defined IRL as only the ganglion cell complex, some other reports defined IRL from the RNFL to the OPL and ORL from the ONL to the RPE layer, and even in some reports, RPE layer was not included in the outer retinal layers. The definition of IRL and ORL in the current study was also used in many previous studies of various diseases including diabetic retinopathy 26,27 , macular edema 15,28 , epiretinal membrane 29 , macular hole 30 , and optic neuropathy 31 . Thus, readers should be careful in interpreting the result of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Some reports defined IRL as only the ganglion cell complex, some other reports defined IRL from the RNFL to the OPL and ORL from the ONL to the RPE layer, and even in some reports, RPE layer was not included in the outer retinal layers. The definition of IRL and ORL in the current study was also used in many previous studies of various diseases including diabetic retinopathy 26,27 , macular edema 15,28 , epiretinal membrane 29 , macular hole 30 , and optic neuropathy 31 . Thus, readers should be careful in interpreting the result of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Although our study's follow up period was only 8 weeks, the results proved to be comparable with the findings of Danesh-Meyer et al [11 abstract], that showed in the series of 40 cases with chiasmatic compressive lesions, with OCT and visual field analysis, that pre and post decompression treatment in patients with thin RNFL did not demonstrate significant improvement in VA and visual field. Min Sun et al [5] Jing Zhang et al [15], as well as Jonathan [16] found with preoperative and postoperative RNFL thickness analysis that eyes with visual defects but normal preoperative RNFL thickness showed a significantly greater improvement in postoperative visual function than those with thin preoperative RNFL thickness. Similarly, Jacob et al [6] demonstrated that circumpapillary RNFL thinning measured by OCT decreased the patient's chances of recovery of initial visual field defect 3 months after treatment.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years it has been established that patients who have objectively measurable RNFL loss and loss of retinal ganglion cell complex (GCC) at the time of surgery for chiasmal compressive lesions are less likely to have recovery of VA or VF after surgery [9][10][11][12][13][14][15][16]. Thinner preoperative RNFL and macular GCC thickness was found to be associated with worse visual acuity (VA) and VF after surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retina is a light receptor tissue of the eye. It consists of several layers, such as the outer nuclear layer (ONL) and the rod and cone photoreceptor layer (PRL) 1,2 . Each layer is highly specialized; therefore, each layer can be a specific target for retinal toxicants.…”
Section: Introductionmentioning
confidence: 99%